2018
DOI: 10.1002/lary.27492
|View full text |Cite
|
Sign up to set email alerts
|

Granulomas of the membranous vocal fold after intubation and other airway instrumentation

Abstract: 4 Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Other etiologies of diffuse laryngeal erythema include traumatic injury from intubation, vocal abuse, and gastroesophageal reflux disease. 15,16 This case represents a unique etiology of laryngotracheal granulomatous disease, and an unusual presentation of sporotrichosis. While respiratory tract sporotrichosis has been described previously, laryngeal involvement is rare.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other etiologies of diffuse laryngeal erythema include traumatic injury from intubation, vocal abuse, and gastroesophageal reflux disease. 15,16 This case represents a unique etiology of laryngotracheal granulomatous disease, and an unusual presentation of sporotrichosis. While respiratory tract sporotrichosis has been described previously, laryngeal involvement is rare.…”
Section: Discussionmentioning
confidence: 96%
“…Other etiologies of diffuse laryngeal erythema include traumatic injury from intubation, vocal abuse, and gastroesophageal reflux disease. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…7 On the contrary, this might also cause false diagnoses of LPRD, which showed that the use of empirical PPI therapy did not lead to any improvement in persistent throat symptoms in 16 weeks or 12 months. 33 (2) An insufficient awareness about related diseases could cause poor efficacies or recurrences in treating such diseases, as antireflux therapy has been accepted in treating some of these diseases, such as laryngeal leukoplakia, 34 laryngeal granuloma 35 and cough. 36 (3) Currently, no perfect diagnostic and treatment methods exist for LPRD: simple ones are not so accurate or effective, such as RSI or RFS evaluations (diagnosis) and behavioural changes (treatment), while accurate or effective ones are always invasive, such as pH-MII monitoring (diagnosis) or antireflux operations (treatment).…”
Section: Open Accessmentioning
confidence: 99%
“…The authors passed an adult fiberoptic scope from the other nostril and then by the side of the ETT to enter the trachea. They succeeded but this can lead to a theoretical trauma to the vocal cord or membranous granuloma of the vocal cord[ 2 ] and/or prolonged hoarseness in postoperative period. In our view a proper preoperative planning of airway is required to avoid such unwanted intraoperative interventions.…”
mentioning
confidence: 99%